A cross-lagged panel analysis of second language achievement and enjoyment - Gao, Minjuan (Frontiers in Psychology, 2023)
Although self-perceived language proficiency has recently been found to influence foreign language enjoyment (FLE), rigorous assessment of the causal relationship between actual second language (L2) achievement and FLE has received relatively little attention. Based on control-value theory, this longitudinal study examined the causal antecedents of the relationship between the L2 achievement of 206 FL learners and their FLE from the perspective of dynamic systems theory and conducted a cross-lagged panel (CLP) analysis using Mplus 8.3 software. Both variables were measured two times over one academic year (10 months) in an English as a foreign language (EFL) course. The Wilcoxon signed-rank test showed significant changes in both variables over time. According to the CLP path model, L2 achievement at Time 1 (T1) appeared to affect subsequent FLE, while FLE at T1 failed to predict L2 achievement at Time 2 (T2). This study provides empirical evidence of the directional effect of L2 achievement on FLE regarding the hypothesized reciprocal effect of the two. Implications for stakeholders in the field of education are discussed.